(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
In the article valuable component of the concept «Memory» is considered in a discourse where ambivalent of the given concept is seen. Depending on the type of a discourse different valuable predicates are used.